Ethics, research and HIV: lessons learned‐ a workshop report. (11th February 2016) - Reznik, DA; Croser, D; Kadrianto, TH; Lavanya, R
Abstract : Assessing risk for transmission of a blood‐borne pathogen requires the use of the hazard and risk model. Infection control is a system that uses a number of individual processes to eliminate or reduce the probability of a hazard occurring. Strategies employed to reduce risk should be rehearsed, used routinely, audited, reviewed, and the results shared. Continuing dental education has improved dental healthcare worker willingness to treat people living with HIV/AIDS (PLWHA) and has decreased negative attitudes and staff fears. Providing care for PLWHA during undergraduate dental school or dental hygiene programme is also associated with a greater willingness to treat. Whether by identifying suspect oral lesions or offering rapid screening tests in the dental setting for HIV, the dental team can play an important role in linkage to confirmatory diagnosis and care with the goal of reducing to zero the number of undiagnosed cases.